Utilization of Banana Pith Starch From Agricultural Waste As A Cationic Coagulant - Yushananta, Prayudhy; Ahyanti, Mei (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The coagulation method is the most commonly used in water treatment. However, long-term use of chemical coagulants can increase the risk of Alzheimer's disease and neurotoxicity, in addition to harming organisms, lowering the pH of the water, corrosion of pipes, and the use of high doses of chlorine. The study synthesized banana pith starch from agricultural waste as a cationic coagulant for river water treatment. Banana pith starch was modified by grafting cations from GTA (3-Chloro-2-hydroxypropyl trimethyl ammonium chloride) into the backbone structure of starch using microwave radiation. Performance tests were carried out on variations in dose (4), speed (3), and stirring time (3). Parameters tested were turbidity, TDS, and color, with four replications. The study found that the synthetic cationic coagulant could reduce turbidity up to 94.4%, while the color and TDS were 87.46% and 57.33%, respectively. The various treatments seemed to work on all test parameters (p less than 0.05). However, the most effective treatment was at a dose of 300 ppm, a stirring speed of 200 rpm, for 5 minutes. Research has proved that banana pith starch can be modified into an effective cationic coagulant to remove colloid compounds in water.Abstrak: Saat ini metode koagulasi merupakan metode yang paling umum digunakan dalam pengolahan air. Namun, penggunaan koagulan kimia jangka panjang dapat meningkatkan risiko penyakit Alzheimer danneurotoksik, selain juga merugikan organisme, pH air menjadi rendah, korosi pipa, penggunaan clorin dosis tinggi. Penelitian bertujuan memanfaatkan pati empulur pisang dari limbah pertanian, sebagai koagulan kationik untuk pengolahan air sungai. Modifikasi pati empulur pisang dilakukan dengan cara mencangkokkan kation dari GTA (3-Chloro-2-hydroxypropyl trimetil amonium klorida) ke dalam struktur tulang punggung pati, menggunakan radiasi gelombang mikro. Pengujian kinerja dilakukan pada variasi dosis (4), kecepatan (3), dan waktu pengadukan (3). Parameter yang diuji adalah kekeruhan, TDS, dan warna, dengan empat kali ulangan. Penelitian mendapatkan bahwa koagulan kationik hasil sintesis mampu mereduksi kekeruhan hingga 94,4%, sedangkan warna dan TDS sebesar 87,46% dan 57,33%. Ragam perlakuan terlihat bekerja pada semua parameter uji (p kurang dari 0,05). Namun begitu, perlakuan paling efektif pada dosis 300 ppm, kecepatan pengadukan 200 rpm, selama 5 menit. Penelitian telah berhasil membuktikan bahwa pati empulur pisang dapat dimodifikasi menjadi koagulan kationik yang efektif untuk menghilangkan senyawa koloid dalam air.